ISOLATION OF PROTEIN FROM THE SPINE VENOM OF PTEROIS VOLITANS FOUND IN THE INDONESIAN OCEAN, USING A HEATING PROCESS, FOR ANTICANCER, ANTIRETROVIRAL, ANTIBACTERIAL, AND ANTIOXIDANT ASSAYS - IBRAHIM, FERA; SAHLAN, MUHAMAD; GINTING, MIKAEL JANUARDI; PRATAMI, DIAH KARTIKA; HERMANSYAH, HERI; WIJANARKO, ANONDHO (International Journal of Applied Pharmaceutics, 2021)
Objective: This research investigates the antibacterial, anticancer, antioxidant, and antiretroviral activities of the lionfish spine poison extract. Methods: Isolation and purification of the phospholipase A2 (PLA2) protein obtained from the spine poison were conducted through the following stages, including, extraction of the venom by sonication, heating, and purification using gradual saturation levels of ammonium sulfate. Furthermore, the purity and concentration of PLA2 were analyzed using the Lowry test and Marinetti’s method, respectively, while its protein content was ascertained through SDS-PAGE. Toxicity was then evaluated employing the brine shrimp lethality test (BSLT), and its anticancer activity was assessed in human cervical carcinoma cells (HeLa cells). Finally, its antioxidant, antibacterial, and antiretroviral activities were analyzed using the DPPH method, agar diffusion test against Salmonella sp. and E. coli, and SRV-2 and RT-qPCR tests, respectively. Results: The protein demonstrated 37.79% inhibition for anticancer activity, IC50 1312 ppm for antioxidant activity, 98.81%, and 89.28% inhibition of E. coli and Salmonella sp. respectively for antibacterial activity and 98.13% inhibition for antiretroviral activity. Conclusion: It can be concluded that lionfish (Pterois volitans) has the potential to be developed as an antioxidant, anticancer, antibacterial, and antiretroviral agent. Furthermore, the pharmacological activity of its spine venom was determined by isolating PLA2 protein from its extract, using an optimum heating temperature of 70 °C and an ammonium sulfate saturation level of 80%.